The Effect of Algebra Finger- Based Brain Gym Method to Improve Student Learning Outcomes - Komarudin Komarudin; Novi Rosmawati; Suherman Suherman (EduMa: Mathematics education learning and teaching, 2019)
This study aims to look at the effect of algebraic finger-based brain gym methods on improving student learning outcomes. This study uses grade VII students MTs. Al-Hidayat Gerning consisting of 4 (four) classes as population, then by cluster random sampling technique obtained class VII A and VII B as research samples. This study uses a quasi-experimental method, the independent variable is the algebraic finger-based brain gym method and the dependent variable is the increase in learning outcomes. Data collection using test techniques, with the research instrument in the form of a matter of description which amounted to 6 questions that have been tested for validity, reliability, level of difficulty, and different power. Data analysis was performed using a t-test of 2 uncorrelated samples. The results revealed that the algebraic finger-based brain gym method has an influence on improving student learning outcomes. This is evidenced by the increase in student learning outcomes after learning with the algebra finger-based brain gym method obtained an average of 56.25 while the improvement in the learning outcomes of the control class gained an average of 37.50. After testing the hypothesis with t-test 2 uncorrelated samples obtained tcount = 5.7774> ttable = 2.0017. So it can be concluded that the algebraic finger-based brain gym method affects the improvement in student learning outcomes